1990
DOI: 10.1002/bbpc.19900940704
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 and Bi2O3 Thin Film Oxygen Sensor Materials

Abstract: Defect Chemistry / Electrical Properties / Interfaces 1 Sensors / Thin FilmsThe electrical conductivity of polycrystalline Ti02 and Bi203, deposited on sapphire substrate by various methods, has been determined as a function of the film thickness, the oxygen partial pressure and the temperature. As a rule, Ti02 films with d 5 30 nm are incoherent after heat treatment, thereby restricting the miniaturization of the planar sensor device. Larger films essentially behave like bulk material with fully ionized oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Oxygen gas sensors are considered to be promising candidates for a wide range of potential applications in automobiles, aerospace, soil respiration, ventilator, and thermal power generation. Particularly, semiconducting metal oxide based chemi-resistive sensors have gained great attention due to advantages such as relatively compact device structure, facile fabrication, and cost-effective and easy integration into integrated circuits. Several studies have been reported on sensors working at room temperature as well as at low temperatures. However, only few reports based on metal oxides have demonstrated stable sensing properties toward oxygen gas at higher temperatures (>200 °C). , Among metal oxides, TiO 2 has been extensively investigated and recognized as an effective material for oxygen gas detection due to their remarkable catalytic properties and superior chemical/mechanical stability. Recently, a great deal of effort has been applied to enhance the gas sensing performance of TiO 2 by developing nanostructured materials with ultrahigh surface-to-volume ratio, elemental doping, and surface modifications to form heterostructures with noble metals and semiconductor nanoparticles. ,, TiO 2 is inherently sensitive to oxygen gas from room temperature to high temperature owing to the high oxygen vacancies present in anatase and rutile crystal structures. Recent studies explored that though TiO 2 based sensor materials are highly sensitive toward oxygen, such materials suffer from high temperature coefficient of resistance (TCR) (i.e., high activation energy). , Hence, one of the major challenges faced by resistive oxygen sensing materials is that though such materials show resistivity changes toward oxygen adsorption, they also respond strongly with temperature which hinders their practical usage under temperature fluctuating conditions.…”
mentioning
confidence: 99%
“…Oxygen gas sensors are considered to be promising candidates for a wide range of potential applications in automobiles, aerospace, soil respiration, ventilator, and thermal power generation. Particularly, semiconducting metal oxide based chemi-resistive sensors have gained great attention due to advantages such as relatively compact device structure, facile fabrication, and cost-effective and easy integration into integrated circuits. Several studies have been reported on sensors working at room temperature as well as at low temperatures. However, only few reports based on metal oxides have demonstrated stable sensing properties toward oxygen gas at higher temperatures (>200 °C). , Among metal oxides, TiO 2 has been extensively investigated and recognized as an effective material for oxygen gas detection due to their remarkable catalytic properties and superior chemical/mechanical stability. Recently, a great deal of effort has been applied to enhance the gas sensing performance of TiO 2 by developing nanostructured materials with ultrahigh surface-to-volume ratio, elemental doping, and surface modifications to form heterostructures with noble metals and semiconductor nanoparticles. ,, TiO 2 is inherently sensitive to oxygen gas from room temperature to high temperature owing to the high oxygen vacancies present in anatase and rutile crystal structures. Recent studies explored that though TiO 2 based sensor materials are highly sensitive toward oxygen, such materials suffer from high temperature coefficient of resistance (TCR) (i.e., high activation energy). , Hence, one of the major challenges faced by resistive oxygen sensing materials is that though such materials show resistivity changes toward oxygen adsorption, they also respond strongly with temperature which hinders their practical usage under temperature fluctuating conditions.…”
mentioning
confidence: 99%
“…What is even more interesting is that titanium dioxide in the form of nanoflowers, both unmodified and sensitized by SnO 2 nanoparticles can exhibit different electrical properties under various gaseous conditions. According to the literature [26,32,3638], there are several possible explanations for this phenomenon. The first is related to formation of titanium vacancies, V Ti , in the flower-like structure during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these features, acceptor intrinsic defects may occur and lead to n→p transitions [3637]. Secondly, according to Nicoloso [38], p-type conductivity is an attribute of the surface rather than the material bulk. The as-obtained pore network and fine grains of titanium dioxide nanoflowers promote high surface-to-volume ratio, which favor the p-type behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A few of its novel applications are based on the surface and catalytic properties. The chemical properties extend its usage as catalyst in chemical reactions [4] and also as a gas sensor [5][6][7]. Due to semi conducting properties, TiO 2 is used in the fabrication of electrodes for photo-electrochemical processes, which are used for conversion of sun light to chemical fuel (H2), photo-electrolysis of water [8]; for conversion of sun light into electricity [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%